The roles of fiscal rules, fiscal councils and fiscal union in EU integration - Lars Calmfors (Research Institute of Industrial Economics (IFN), 2015)
EU-level fiscal rules have not been able to prevent the large-scale accumulation of government debt in many eurozone countries. One explanation was major flaws in the rules. Some of these flaws have now been corrected. But the failure of the rules depended also on fundamental problems of time inconsistency. The same time-inconsistency problems that the rules were designed to address also apply to the rules themselves. Fiscal councils may be subject to less of such problems than rules. Still it is unlikely that a monetary union where bail-outs of governments are part of the system is viable in the long run. The sustainability of the euro may require a restoration of the no-bail-out clause and a strengthening of the banking union in ways that would allow it to cope with the financial repercussions that could arise from allowing government bankruptcies.
Keywords: F55; E61; E63; 330; Fiscal rules; fiscal councils; European integration